Pelatihan Cepat dan Mudah Membaca Al-Qur’an bagi Tutor PAI melalui Metode Tsaqifa di Universitas Jambi - Abdul Muid; Fahmi Huda, Rofiazka; Jufri, Salman; Hasani, Salman (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Reading the Holy Qur’an is still challenging, even for adults. Many students need help when they intend to start reading the Qur'an despite having previously learned Iqra. Therefore, this training aims to improve students’ motivation to read the Qur’an using an effective and efficient method. The chosen solution to address this phenomenon is the Tsaqifa method introduced by Umar Taqwim with five meetings. Partners in this action are students from the Universitas Jambi who serve as Islamic Education tutors for their peers. The training was conducted at the Universitas Jambi in August 2023 utilizing the Participatory Action Research method developed with the Kemmis & McTaggart approach. The post-training results indicate an improvement in motivation to learn how to read the Qur’an, and the partners are capable of understanding and applying the Tsaqifa method to their colleagues and friends.